2008
DOI: 10.1021/es702463a
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Osmosis Desalting of Inland Brackish Water of High Gypsum Scaling Propensity: Kinetics and Mitigation of Membrane Mineral Scaling

Abstract: The potential for mineral scaling that may limit the generation of new potable water resources by reverse osmosis (RO), from inland brackish water of high gypsum scaling propensity, was experimentally explored via flux decline measurements and real-time RO membrane surface imaging. Antagonistic gypsum and calcium carbonate scaling kinetics were demonstrated for high-sulfate brackish water desalting. RO scaling studies with brackish water from the California San Joaquin Valley (approximately 10 000 mg/L total d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(63 citation statements)
references
References 18 publications
2
61
0
Order By: Relevance
“…However in presence of calcium, saturation and hence scaling due to calcium sulfate is very likely to happen (Rahardianato et al, 2008;Sheikholesami, 2003a;Sheikholesami, 2004). Precipitative softening processes were found to be very effective in removal of calcium, magnesium, carbonate, and silica.…”
Section: Precipitation Softening For Brine Treatment In Zero Liquid Dmentioning
confidence: 99%
See 1 more Smart Citation
“…However in presence of calcium, saturation and hence scaling due to calcium sulfate is very likely to happen (Rahardianato et al, 2008;Sheikholesami, 2003a;Sheikholesami, 2004). Precipitative softening processes were found to be very effective in removal of calcium, magnesium, carbonate, and silica.…”
Section: Precipitation Softening For Brine Treatment In Zero Liquid Dmentioning
confidence: 99%
“…In addition sulfate may result from biological oxidation of reduced sulfur species. As a result the different aspects of scaling by calcium sulfate and calcium carbonate has been intensively studied (Sheikholesami, 2003a;Sheikholesami, 2003b;Rahardianato et al, 2008).…”
Section: Scaling and Foulingmentioning
confidence: 99%
“…Effectiveness of several commercial antiscalants against gypsum scale formation was evaluated by Shih et al [10]. Based on precipitation studies, Rahardianto [11] found that increasing bicarbonate concentrations led to minimized membrane scaling with gypsum. Amjad [12] examined the inhibition of gypsum precipitation by a variety of polymeric materials and concluded that compared to polymers, surfactants perform poorly against gypsum precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…reverse osmosis (RO) and nanofiltration (NF) [1][2][3]. Scaling is an impediment for the application of high pressure membrane process since it causes a significant decline of permeate flux and irreversible damage to the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, scaling in RO and NF process is due to the supersaturation of salts at the interface of the membrane and feed solution, followed by crystallization and growth [3]. Various factors, such as temperature, hydrodynamic conditions, pH, and interaction of solutes, can affect the formation of scaling [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%